Legal Mechanism of State Administration of the European Integration Process in Ukraine - Orel, Oleksii (Public Policy and Accounting, 2024)
Ukraine is currently negotiating with the EU regarding accession, which involves conducting a screening for compliance with EU law. To improve the legal mechanism of state administration in the European integration process in Ukraine under the chapter «financial and budgetary provisions» it is proposed to amend the Budget Code of Ukraine by replacing «principles of the budgetary system» with «budgetary principles». It is also suggested to substitute the principle of efficiency and effectiveness with the principle of sound management of budget funds and productivity. Additionally, Chapter 18 «Liability and Measures for Violations of Budget Legislation» of the Budget Code of Ukraine should include liability for non-compliance with the principle of sound management of budget funds and productivity. To enhance state governance of the European integration process in Ukraine, it is proposed to establish a Public Finance Office within the Cabinet of Ministers of Ukraine in accordance with the European Commission’s recommendation to form a coordinating body for administrative processes within the own resources system to raise awareness among key parties involved. To address a significant number of gaps in public finance management – a key area in the context of good governance – it is proposed to develop the structure of a Law «On Public Finance Management in Ukraine». To fulfil the European Commission’s recommendations under the section «financial control» it is proposed to fully implement into Ukraine’s audit practice the International Standards of Supreme Audit Institutions (ISSAI) and Global Internal Audit Standards (GIAS), and legally enshrine these standards in Ukraine’s regulatory audit framework. A critical analysis of the Law of Ukraine «On the Basic Principles of State Financial Control in Ukraine» has been conducted, identifying its significant shortcomings. Based on this analysis and European practices in financial control, the structure of a new Law of Ukraine «On State Financial Control in Ukraine» is proposed.